2020
DOI: 10.3389/fpsyg.2020.01803
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Chinese Middle School Students’ Motivation Using the Reduced Instructional Materials Motivation Survey (RIMMS): A Validation Study in the Adaptive Learning Setting

Abstract: Valid measures of student motivation can inform the design of learning environments to engage students and maximize learning gains. This study validates a measure of student motivation, the Reduced Instructional Materials Motivation Survey (RIMMS), with a sample of Chinese middle school students using an adaptive learning system in math. Participants were 429 students from 21 provinces in China. Their ages ranged from 14 to 17 years old, and most were in 9th grade. A confirmatory factor analysis (CFA) validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The usage of the Attention, Relevance, Confidence, and Satisfaction (ARCS) (Keller, 2009) model of motivation to utilize learned material RIMMS scale (Loorbach et al, 2015) may have been ineffective in the Chinese context. While the present study used an adapted version of the scale already translated into Mandarin Chinese (Wang et al, 2020), representatives reported high levels of transfer intention across all conditions. This could be due to several factors.…”
Section: Arcs Measurementioning
confidence: 94%
See 2 more Smart Citations
“…The usage of the Attention, Relevance, Confidence, and Satisfaction (ARCS) (Keller, 2009) model of motivation to utilize learned material RIMMS scale (Loorbach et al, 2015) may have been ineffective in the Chinese context. While the present study used an adapted version of the scale already translated into Mandarin Chinese (Wang et al, 2020), representatives reported high levels of transfer intention across all conditions. This could be due to several factors.…”
Section: Arcs Measurementioning
confidence: 94%
“…Representatives in the active reflection condition were given access to the instructional material, plus participated in brief active reflection sessions with a manager after each learning session. Representatives in the feedback condition were given access to the instructional material, participated in brief active reflection sessions with a manager after each learning session (Villena Taranilla et al, 2019;Wang et al, 2020), and they also received feedback on how they performed, as well as ways to improve going forward, from their manager in a group setting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…People’s actions, desires, and needs are all derived from motivation to drive people’s behaviors or arouse someone’s desire to do something ( Elliot and Covington, 2001 ; Vansteenkiste et al, 2020 ). Learning motivation is the degree of students’ willingness to continue to learn hard ( Wang et al, 2020 ). Motivation is one of the primary factors that drive students to learn.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Learning and motivation are overly complex aspects of human behaviour (Law et al, 2010;Wang et al, 2020). Motivation is a key factor that encourages students to learn (Ling et al 2020).…”
Section: Introductionmentioning
confidence: 99%